Heterogeneous composite catalyst with surface treated by using amine compound, method of manufacturing same, and method of preparing chiral compound using same
A surface-treated heterogeneous composite catalyst with nitrogen-containing hydrocarbons enhances enantiomer selectivity by controlling active site ratios, addressing the challenge of forming optimal chiral sites in heterogeneous catalysts, thus improving catalytic efficiency and industrial applicability.
Patent Information
- Application Number
- KR1020230087601
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-07-06
- Publication Date
- 2026-11-05
- Estimated Expiration
- 2043-07-06
AI Technical Summary
Existing heterogeneous catalysts face challenges in achieving high enantiomer selectivity due to the complexity of forming optimal chiral active sites, which hinders their industrial application and requires a simpler method to improve selectivity.
A heterogeneous composite catalyst is developed by surface-treating metal nanoparticles with a nitrogen-containing hydrocarbon compound, such as aliphatic or aromatic amines, to control the ratio of high-coordinated to low-coordinated active sites, enhancing enantiomer selectivity.
The catalyst improves catalytic activity and enantiomer selectivity through surface treatment, allowing for efficient and selective production of one enantiomer, thereby improving industrial applicability and cost-effectiveness.
Smart Images

Figure 112023074356914-PAT00034_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a heterogeneous composite catalyst surface-treated with an amine compound, a method for manufacturing the same, and a method for synthesizing a chiral compound using the same. Background Technology
[0002] Chiral compounds are carbon-based organic molecules with a three-dimensional structure in which the four parts bonded to the carbon are all different; they are compounds that have mirror-image isomers with the same molecular formula but cannot be superimposed through rotation. The two mirror-image isomers have a symmetrical relationship as if reflected in a mirror, and since they have the same chemical formula and molecular weight, their physical and chemical properties are generally identical.
[0003] Biomolecules found in nature, including the human body, such as proteins and DNA, possess monochirality. Consequently, depending on the case, two enantiomers can exhibit different physiological activities upon biological absorption of the monochiral biomolecule. Chiral compounds are utilized as raw materials and intermediates in the fine chemical industry, including pharmaceuticals, pesticides, and cosmetics; in this context, the physiological activities of the two distinct enantiomers within these compounds are being studied and verified separately. Consequently, the demand for technologies to produce monochiral enantiomers has steadily increased.
[0004] Production technologies for producing a single enantiomer can be broadly divided into two categories. The first involves separating the two enantiomers through a separation process following a general racemic process in which the two enantiomers are produced in a 1:1 ratio. However, this technology has limitations, such as the fact that half of the product must be discarded and additional costs incurred during the separation process to separate two enantiomers with identical physical and chemical properties. To overcome these limitations, technologies for selectively producing one of the two enantiomers through enantiomer-selective catalytic reactions are being researched and attempted in various fields, including microbial-based catalysts, photocatalysts, homogeneous catalysts, and heterogeneous catalysts. Among these, heterogeneous catalysts offer significant advantages in terms of ease of product-catalyst separation, catalyst reusability, and stability for industrial process applications; however, because they generally exhibit lower enantiomer selectivity compared to other catalyst systems, research is being conducted to control the characteristics of the components of heterogeneous catalysts to improve this aspect.
[0005] Meanwhile, to enhance enantiomer selectivity in structure-sensitive enantiomer-selective heterogeneous catalytic reaction systems, the heterogeneous catalyst components, such as metal nanoparticles and supports, must be precisely controlled from the catalyst synthesis stage. However, technologies for generating optimal chiral active sites on heterogeneous catalyst surfaces face limitations in terms of industrial application because mass production is difficult due to the complexity of the catalyst production process.
[0006] Therefore, there is a need to develop a technology that can solve the aforementioned problems and improve enantiomer selectivity by forming optimal chiral active sites on heterogeneous supported catalysts through a simple method. The problem to be solved
[0007] The objective of the present invention is to provide a heterogeneous composite catalyst capable of improving enantiomer selectivity by forming optimal chiral active sites on a heterogeneous supported catalyst that has already been synthesized in large quantities through a simple surface treatment method, and a method for manufacturing the same.
[0008] Another objective of the present invention is to provide a heterogeneous composite catalyst and a method for manufacturing the same, which can control the high-coordinated number site / low-coordinated number site (WC / UC) ratio through surface amine treatment and thereby improve the enantiomer selectivity of the catalyst.
[0009] Another objective of the present invention is to provide a method for synthesizing a chiral compound selectively formed using the heterogeneous composite catalyst of the present invention. means of solving the problem
[0010] According to one aspect of the present invention, a heterogeneous composite catalyst is provided comprising: a metal oxide; metal nanoparticles supported on the metal oxide; and a nitrogen-containing hydrocarbon compound formed on a portion of the surface of the metal nanoparticles.
[0011] In addition, the nitrogen-containing hydrocarbon compound may cover some of the active sites exposed on the surface of the metal nanoparticles.
[0012] In addition, the active site may include a well-coordinated site (WC) and an under-coordinated site (UC).
[0013] In addition, the nitrogen-containing hydrocarbon compound may be located at the low-coordination site active site and may cover the low-coordination site active site.
[0014] In addition, as the nitrogen-containing hydrocarbon compound increases, the ratio of high-coordinated active sites to low-coordinated active sites (WC / UC) may increase.
[0015] In addition, the above heterogeneous composite catalyst may be used to selectively produce one of the enantiomers.
[0016] In addition, the selectivity of the enantiomer may change depending on the ratio (WC / UC) of the high-coordinate active site to the low-coordinate active site.
[0017] In addition, the nitrogen-containing hydrocarbon compound may include -NH, -CH2, and -CH3 groups.
[0018] In addition, the nitrogen-containing hydrocarbon compound can be produced by heat-treating an amine compound formed on a portion of the surface of the metal nanoparticle.
[0019] In addition, the above amine compound may include one or more selected from aliphatic amine compounds and aromatic amine compounds.
[0020] In addition, the above-mentioned aliphatic amine compound may be a compound represented by the structural formula 1 below:
[0021] [Structural Formula 1]
[0022]
[0023] In the above structural formula 1,
[0024] R 1 is a linear or branched C1 to C15 alkylene group, and
[0025] R 2 is an atom bond, or And,
[0026] R 3 The valence is a linear or branched C1 to C15 alkylene group, and
[0027] X is a hydrogen atom or -NH2.
[0028] In addition, the above aromatic amine compound may be a compound represented by the structural formula 2 below:
[0029] [Structural Formula 2]
[0030]
[0031] In the above structural formula 2,
[0032] R 4 The valence is a linear or branched C1 to C5 alkylene group or a C6 to C20 arylene group, and
[0033] R 5 is an atom bond, or And,
[0034] R 6 is a C6 to C20 arylene group, and
[0035] R 7 The valence bond is a linear or branched C1 to C5 alkylene group, or a C6 to C20 arylene group, and
[0036] Y is a hydrogen atom or -NH2.
[0037] In addition, the metal oxide may include one or more selected from the group consisting of silica (SiO2), alumina (Al2O3), silica-alumina (SiO-2-Al2O3), titanium oxide (TiO2), zirconium oxide (ZrO2), cerium oxide (CeO2), and magnesium oxide (MgO).
[0038] In addition, the metal nanoparticles may include one or more selected from the group consisting of platinum (Pt), palladium (Pd), ruthenium (Ru), rhodium (Rh), iridium (Ir), rhenium (Re), cobalt (Co), tungsten (W), vanadium (V), nickel (Ni), gold (Au), silver (Ag), and copper (Cu).
[0039] In addition, the heterogeneous composite catalyst may further include a chiral modifier formed on other parts of the surface of the metal nanoparticles.
[0040] In addition, the chiral modifier may include one or more selected from the group consisting of quinoline-based optical isomers, indole-based optical isomers, naphthylene-based optical isomers, indole-based optical isomers, and pyrrolidine-based optical isomers.
[0041] In addition, the chiral modifier may include one or more selected from the group consisting of compounds represented by the following chemical formulas 1 to 22.
[0042]
[0043]
[0044] According to another aspect of the present invention, a method for manufacturing a heterogeneous composite catalyst is provided, comprising: (a) mixing and stirring a metal precursor, a metal oxide, and a first solvent to prepare a first mixture; (b) removing the first solvent from the first mixture and grinding it to prepare a first powder; (c) heat-treating the first powder under an inert gas to prepare a metal oxide supported with metal nanoparticles; (d) mixing the metal oxide supported with metal nanoparticles, an amine compound, and a second solvent to prepare a second mixture; (e) removing the second solvent from the second mixture and grinding it to prepare a second powder; and (f) heat-treating the second powder to prepare the heterogeneous composite catalyst.
[0045] In addition, the method for manufacturing the heterogeneous composite catalyst may further include, after step (f), (g) a step of reducing the heterogeneous composite catalyst in the presence of hydrogen; and (h) a step of mixing the reduced heterogeneous composite catalyst with a chiral modifier and stirring in the presence of hydrogen to produce a heterogeneous composite catalyst containing a chiral modifier.
[0046] According to another aspect of the present invention, a method for synthesizing a chiral compound is provided, comprising the step of selectively preparing a chiral compound of any one of enantiomers by contacting a compound represented by the structural formula 3 below with the heterogeneous composite catalyst;
[0047] [Structural Formula 3]
[0048]
[0049] In the above structural formula 3,
[0050] R 8 and R 9 Each is independently a halogen atom, a substituted or unsubstituted C1 to C5 alkyl group, or a substituted or unsubstituted C6 to C30 aryl group, or forms a ring with an adjacent group, and
[0051] A is -(C=O)-, -CR 10 R 11 -, -NR 12 - or -O- and,
[0052] Here, R 10 and R 11 Each is independently a hydrogen atom, a halogen atom, or a substituted or unsubstituted alkoxy group, and
[0053] R 12 is a hydrogen atom, or a substituted or unsubstituted alkyl group, and
[0054] The group corresponding to the above substitution is a C1 to C5 alkyl group or a C6 to C14 aryl group, and
[0055] n is an integer from 1 to 3, and
[0056] If n is 2 or greater, 2 or more A's are identical or different from each other. Effects of the invention
[0057] The heterogeneous composite catalyst of the present invention can improve catalytic activity and enantiomer selectivity compared to before surface treatment by controlling active sites exposed on the surface of metal nanoparticles through the treatment of the catalyst surface with an amine organic material.
[0058] In addition, the heterogeneous composite catalyst of the present invention can easily modify a large amount of the heterogeneous composite catalyst through a post-treatment method, thereby securing price competitiveness by improving the efficiency of the catalytic reaction system. Brief explanation of the drawing
[0059] These drawings are for reference to explain exemplary embodiments of the present invention, and therefore, the technical concept of the present invention should not be interpreted as being limited to the attached drawings. FIG. 1 is a schematic diagram showing the concept of a surface amine treatment method according to an embodiment of the present invention and the resulting heterogeneous composite catalyst surface active site modification effect. Figure 2 is a STEM image of the OAm-Pt-0 catalyst of Comparative Example 1 of the present invention and the OAm-Pt-a (a = 05, 10, 30, 50) catalyst of Examples 1-1 to 1-4, along with a platinum nanoparticle size distribution. FIG. 3a is the CO adsorption infrared spectroscopic spectrum of the OAm-Pt-0 catalyst of Comparative Example 1 of the present invention and the OAm-Pt-a (a = 05, 10, 30, 50) catalyst of Examples 1-1 to 1-4. Figure 3b is a diagram showing WC sites (Terrace sites) and UC sites (Defect sites). Figure 3c is a schematic diagram showing a comparison of the adsorption of chiral modifiers at the WC site and UC site. FIG. 4 is the transmitted infrared spectroscopic spectrum of the OAm-Pt-0 catalyst of Comparative Example 1 of the present invention and the OAm-Pt-a (a = 05, 10, 30, 50) catalyst of Examples 1-1 to 1-4. Figure 5 is an elemental mapping image based on energy-dispersive spectroscopy of the OAm-Pt-50 catalyst of Examples 1-4 of the present invention. Figure 6 shows the conversion rate according to the reusable catalytic reaction of the OAm-Pt-50 catalyst of Examples 1-4 of the present invention and eeThis is a graph summarizing [it]. FIG. 7a shows the catalytic reaction according to hydrogen pressure conditions using the OAm-Pt-0 catalyst of Comparative Example 1 of the present invention and the OAm-Pt-50 catalyst of Examples 1-4. ee This is a graph showing . FIG. 7b shows the conversion rate (won) in the enantiomer-selective hydrogenation of methyl pyruvate with respect to the OAm-Pt-50 catalyst using the OAm-Pt-50 catalyst of Examples 1-4 of the present invention and ee This is a graph showing the time dependence of (rectangle). FIG. 8a shows the catalytic reaction after enantiomer-selective hydrogenation of the OAm-Pt-0 catalyst of Comparative Example 1 of the present invention and the OAm-Pt-a (a = 05, 10, 30, 50) catalysts of Examples 1-1 to 1-4. ee This is a graph showing . FIG. 8b is a diagram showing the production of a chiral compound through a mirror image isomer-selective heterogeneous complex catalyst reaction of the present invention. FIG. 9 is a catalytic reaction after enantiomer-selective hydrogenation reaction of catalysts according to Examples 1-4, Examples 2-1 to 2-4, Comparative Example 1 and Comparative Example 2 of the present invention. ee This is a graph showing . Specific details for implementing the invention
[0060] Hereinafter, embodiments of the present invention will be described in detail with reference to the attached drawings so that those skilled in the art can easily implement the present invention.
[0061] However, the following description is not intended to limit the present invention to specific embodiments, and detailed descriptions of related prior art are omitted if it is determined that such detailed descriptions could obscure the essence of the present invention.
[0062] The terms used herein are merely for describing specific embodiments and are not intended to limit the invention. The singular expression includes the plural expression unless the context clearly indicates otherwise. In this application, terms such as "comprising" or "having" are intended to indicate the presence of the features, numbers, steps, actions, components, or combinations thereof described in the specification, and should be understood as not precluding the existence or addition of one or more other features, numbers, steps, actions, components, or combinations thereof.
[0063] Additionally, terms including ordinal numbers, such as "first," "second," etc., used below may be used to describe various components, but said components are not limited by said terms. These terms are used solely for the purpose of distinguishing one component from another. For example, without departing from the scope of the present invention, the first component may be named the second component, and similarly, the second component may be named the first component.
[0064] Furthermore, when it is stated that a component is "formed" or "laminated" on another component, it should be understood that while it may be formed or laminated by being directly attached to the entire surface or one surface of the other component, there may also be other components present in between.
[0065] Hereinafter, a heterogeneous composite catalyst surface-treated with an amine compound of the present invention, a method for manufacturing the same, and a method for synthesizing a chiral compound using the same will be described in detail. However, this is presented as an example and the present invention is not limited thereto, and the present invention is defined only by the scope of the claims set forth below.
[0066] FIG. 1 is a schematic diagram showing the concept of a surface amine treatment method according to an embodiment of the present invention and the resulting heterogeneous composite catalyst surface active site modification effect.
[0067] Referring to FIG. 1, the present invention provides a heterogeneous composite catalyst comprising: a metal oxide; metal nanoparticles supported on the metal oxide; and a nitrogen-containing hydrocarbon compound formed on a portion of the surface of the metal nanoparticles.
[0068] In addition, the nitrogen-containing hydrocarbon compound may cover some of the active sites exposed on the surface of the metal nanoparticles.
[0069] Figure 3b is a diagram showing WC sites (Terrace sites) and UC sites (Defect sites), and Figure 3c is a schematic diagram showing a comparison of adsorption of a chiral modifier at WC sites and UC sites.
[0070] Referring to FIGS. 3b and 3c, the active site may include a well-coordinated site (WC) and an under-coordinated site (UC).
[0071] Here, well-coordinated sites (WC) are sites that form a planar terrace on the surface of metal nanoparticles, and under-coordinated sites (UC) are sites that do not form a planar terrace and form a defect.
[0072] The above high-coordinate and low-coordinate sites can be distinguished through infrared spectroscopy.
[0073] In addition, the nitrogen-containing hydrocarbon compound may be located at the low-coordination site active site and may cover the low-coordination site active site.
[0074] In addition, as the nitrogen-containing hydrocarbon compound increases, the ratio of high-coordinated active sites to low-coordinated active sites (WC / UC) may increase.
[0075] In addition, the above heterogeneous composite catalyst may be used to selectively produce one of the enantiomers.
[0076] In addition, the selectivity of the enantiomer may change depending on the ratio (WC / UC) of the high-coordinate active site to the low-coordinate active site.
[0077] In addition, the nitrogen-containing hydrocarbon compound may include -NH, -CH2, and -CH3 groups.
[0078] In addition, the nitrogen-containing hydrocarbon compound may include an amine compound.
[0079] In addition, the nitrogen-containing hydrocarbon compound can be produced by heat-treating an amine compound formed on a portion of the surface of the metal nanoparticle.
[0080] In addition, the above amine compound may include one or more selected from aliphatic amine compounds and aromatic amine compounds.
[0081] In addition, the above-mentioned aliphatic amine compound may be a compound represented by the structural formula 1 below:
[0082] [Structural Formula 1]
[0083]
[0084] In the above structural formula 1,
[0085] R 1 is a linear or branched C1 to C15 alkylene group, and
[0086] R 2 is an atom bond, or And,
[0087] R 3The valence is a linear or branched C1 to C15 alkylene group, and
[0088] X is a hydrogen atom or -NH2.
[0089] In addition, the above aromatic amine compound may be a compound represented by the structural formula 2 below:
[0090] [Structural Formula 2]
[0091]
[0092] In the above structural formula 2,
[0093] R 4 The valence is a linear or branched C1 to C5 alkylene group or a C6 to C20 arylene group, and
[0094] R 5 is an atom bond, or And,
[0095] R 6 is a C6 to C20 arylene group, and
[0096] R 7 The valence bond is a linear or branched C1 to C5 alkylene group, or a C6 to C20 arylene group, and
[0097] Y is a hydrogen atom or -NH2.
[0098] In addition, the above amine compound may be derived from an amine-based compound comprising one or more selected from the group consisting of oleylamine, benzylamine, ethylenediamine, tert-butylamine, and cyclohexylamine.
[0099] In addition, the metal oxide may include one or more selected from the group consisting of silica (SiO2), alumina (Al2O3), silica-alumina (SiO-2-Al2O3), titanium oxide (TiO2), zirconium oxide (ZrO2), cerium oxide (CeO2), and magnesium oxide (MgO).
[0100] In addition, the metal nanoparticles may include one or more selected from the group consisting of platinum (Pt), palladium (Pd), ruthenium (Ru), rhodium (Rh), iridium (Ir), rhenium (Re), cobalt (Co), tungsten (W), vanadium (V), nickel (Ni), gold (Au), silver (Ag), and copper (Cu).
[0101] In addition, the average particle size of the metal nanoparticles may be 1 to 20 nm. Preferably, it may be 1 to 10 nm. If the average particle size of the metal nanoparticles is less than 1 nm, it is undesirable because the metal nanoparticles are too small to perform catalytic activity, and if it exceeds 20 nm, it is undesirable because the metal nanoparticles are not well dispersed and cannot exhibit high catalytic efficiency.
[0102] Additionally, the average particle size of the metal nanoparticles may be a length calculated by the chemisorption method. The average particle size of the metal nanoparticles may be the length of the longest line connecting two points on the surface of the metal nanoparticles in an image measured by a transmission electron microscope.
[0103] In addition, the metal nanoparticles may exhibit a spherical shape. In this specification, the term "spherical" does not mean only a perfect sphere, but may include a shape that appears spherical under a transmission electron microscope due to a polyhedral shape formed by multiple faces.
[0104] In addition, the metal nanoparticles may comprise one of solid particles containing a single metal, solid particles containing two or more metals, core-shell particles containing two or more metals, yolk-shell particles containing two or more metals, or porous particles containing one or two or more metals.
[0105] In addition, the heterogeneous composite catalyst may contain 0.1 to 10 parts by weight, preferably 0.3 to 6 parts by weight, of the metal nanoparticles based on 100 parts by weight of the sum of the metal oxide and the metal nanoparticles. If the amount of metal nanoparticles is less than 0.1 parts by weight, the effect resulting from using the metal nanoparticles (excellent selectivity for enantiomers) is negligible and is undesirable; if the amount exceeds 10 parts by weight, the effect is negligible relative to the amount of metal nanoparticles used, making it economically inefficient and is therefore undesirable.
[0106] In addition, the heterogeneous composite catalyst may further include a chiral modifier formed on other parts of the surface of the metal nanoparticles.
[0107] Here, the chiral modifier adsorbed on the surface of the metal nanoparticles that are not bonded with amine refers to an organic compound capable of newly imparting chirality to the surface of the non-chiral metal nanoparticles. Specifically, in this specification, the chiral modifier refers to a substance capable of imparting chiral selectivity by forming chiral active sites on the surface of the metal nanoparticles, thereby enabling the more selective production of one isomer during the process in which the reactants are formed into two enantiomers.
[0108] In addition, the chiral modifier may include one or more selected from the group consisting of quinoline optical isomers, indole optical isomers, naphthylene optical isomers, indole optical isomers, and pyrrolidine optical isomers, preferably quinoline optical isomers.
[0109] In addition, the chiral modifier may include one or more selected from the group consisting of compounds represented by the following chemical formulas 1 to 22.
[0110]
[0111]
[0112] In addition, the chiral modifier may include one or more selected from the group consisting of cinchonidine, cinchonine, quinine, and quinidine.
[0113] In addition, the metal on the surface of the metal nanoparticles can be bonded to the chiral modifier by covalent or coordinate bonding.
[0114] According to another aspect of the present invention, a method for preparing a heterogeneous composite catalyst is provided, comprising: (a) mixing and stirring a metal precursor, a metal oxide, and a first solvent to prepare a first mixture; (b) removing the first solvent from the first mixture and grinding it to prepare a first powder; (c) heat-treating the first powder under an inert gas to prepare a metal oxide supported with metal nanoparticles; (d) mixing the metal oxide supported with metal nanoparticles, an amine compound, and a second solvent to prepare a second mixture; (e) removing the second solvent from the second mixture and grinding it to prepare a second powder; and (f) heat-treating the second powder to prepare the heterogeneous composite catalyst.
[0115] In addition, the method for manufacturing the heterogeneous composite catalyst may further include, after step (f), (g) a step of reducing the heterogeneous composite catalyst in the presence of hydrogen; and (h) a step of mixing the reduced heterogeneous composite catalyst with a chiral modifier and stirring in the presence of hydrogen to produce a heterogeneous composite catalyst containing a chiral modifier.
[0116] In addition, the heat treatment of step (f) may be performed at 170 to 230 ℃, preferably 190 to 210 ℃. If the heat treatment of step (f) is performed at less than 170 ℃, the catalyst surface activation and impurity removal processes do not proceed smoothly, which is undesirable. If it exceeds 230 ℃, decomposition or damage to nitrogen-containing hydrocarbon compounds present on the catalyst surface may occur, which may lead to a decrease in performance in the chiral catalytic reaction, which is also undesirable.
[0117] According to another aspect of the present invention, a method for synthesizing a chiral compound is provided, comprising the step of selectively preparing a chiral compound of any one of enantiomers by contacting a compound represented by the structural formula 3 below with the heterogeneous composite catalyst;
[0118] [Structural Formula 3]
[0119]
[0120] In the above structural formula 3,
[0121] R 8 and R 9 Each is independently a halogen atom, a substituted or unsubstituted C1 to C5 alkyl group, or a substituted or unsubstituted C6 to C30 aryl group, or forms a ring with an adjacent group, and
[0122] A is -(C=O)-, -CR 10 R 11 -, -NR 12 - or -O- and,
[0123] Here, R 10 and R 11 Each is independently a hydrogen atom, a halogen atom, or a substituted or unsubstituted alkoxy group, and
[0124] R 12 is a hydrogen atom, or a substituted or unsubstituted alkyl group, and
[0125] The group corresponding to the above substitution is a C1 to C5 alkyl group or a C6 to C14 aryl group, and
[0126] n is an integer from 1 to 3, and
[0127] If n is 2 or greater, 2 or more A's are identical or different from each other.
[0128] The compound represented by the above structural formula 3 may include one or more selected from the group consisting of compounds represented by the following chemical formulas 23 to 35.
[0129]
[0130]
[0131] In addition, the compound represented by the above structural formula 3 may include α-keto esters, and preferably may include one or more selected from the group consisting of the following compounds.
[0132]
[0133] In addition, the above enantiomer may include a compound represented by structural formula 4 below and a compound represented by structural formula 5 below.
[0134] [Structural Formula 4]
[0135]
[0136] [Structural Formula 5]
[0137]
[0138] In the above structural formulas 4 and 5,
[0139] R 13 , R 14 , R 15 and R 16 Each is independently a halogen atom, a substituted or unsubstituted C1 to C5 alkyl group, or a substituted or unsubstituted C6 to C30 aryl group, or forms a ring with an adjacent group, and
[0140] A is -(C=O)-, -CR17 R 18 -, -NR 19 - or -O- and,
[0141] R 17 and R 18 Each is independently a hydrogen atom, a halogen atom, or a substituted or unsubstituted alkoxy group, and
[0142] R 19 is a hydrogen atom, or a substituted or unsubstituted alkyl group, and
[0143] n is an integer from 1 to 3, and
[0144] If n is 2 or greater, 2 or more A's are identical or different from each other.
[0145] In addition, the method for synthesizing the chiral compound can produce more of one selected from the group consisting of the compound represented by structural formula 4 and the compound represented by structural formula 5 than of the other.
[0146] [Example]
[0147] Hereinafter, preferred embodiments of the present invention will be described. However, this is for illustrative purposes only and does not limit the scope of the present invention.
[0148] Preparation Example: Preparation of heterogeneous composite catalyst (before amine treatment)
[0149] A heterogeneous platinum catalyst prior to amine treatment was prepared using a wet impregnation method. First, 66 mg of a platinum precursor (Platinum(II) acetylacetonate) was completely dissolved in 10 mL of acetone. 1 g of alumina was added to the solution, placed on a stirrer, and stirred at 200 rpm for 12 hours while maintaining the temperature at 40 ℃. After all the solvent had evaporated, the formed solid was ground into a fine powder and dried in an oven at 80 ℃ for 12 hours. Subsequently, the solid was transferred to a high-temperature synthesis vessel and subjected to a heat treatment process at 350 ℃ for 3 hours while flowing argon gas to prepare the heterogeneous platinum catalyst prior to amine treatment.
[0150] Example: Surface amine-treated heterogeneous composite catalyst
[0151] Example 1: Heterogeneous composite catalyst surface-treated with oleylamine
[0152] Example 1-1: OAm-Pt-05 catalyst, oleylamine 0.5 mmol
[0153] 1 g of the platinum catalyst synthesized in the preparation example and 10 mL of isopropyl alcohol were placed in a container and completely dispersed using an ultrasonic disperser for 10 minutes. 0.5 mmol of oleylamine (OAm) was added to the solution, placed on a stirrer, and stirred at 500 rpm at room temperature for 12 hours. Afterward, the supernatant was removed using a centrifuge, and the solid was completely dried under vacuum at room temperature. After grinding the solid into a fine powder, 0.5 g portions were transferred to a high-temperature synthesis container, and the OAm-Pt-05 catalyst was prepared through a heat treatment process at 350 °C for 1 hour. At this time, the platinum content contained in the OAm-Pt-05 catalyst was 3.0 wt%.
[0154] Examples 1-2: OAm-Pt-10 catalyst, oleylamine 1.0 mmol
[0155] 1 g of the platinum catalyst synthesized in the preparation example and 10 mL of isopropyl alcohol were placed in a container and completely dispersed using an ultrasonic disperser for 10 minutes. 1.0 mmol of oleylamine (OAm) was added to the solution, placed on a stirrer, and stirred at 500 rpm at room temperature for 12 hours. Afterward, the supernatant was removed using a centrifuge, and the solid was completely dried under vacuum at room temperature. After grinding the solid into a fine powder, 0.5 g portions were transferred to a high-temperature synthesis container, and the OAm-Pt-10 catalyst was prepared through a heat treatment process at 350 °C for 1 hour. At this time, the platinum content contained in the OAm-Pt-10 catalyst was 2.8 wt%.
[0156] A platinum catalyst was prepared in the same manner as in Example 1-1 above, except that the amount of oleylamine added during the manufacturing process was 1.0 mmol.
[0157] Examples 1-3: OAm-Pt-30 catalyst, oleylamine 3.0 mmol
[0158] 1 g of the platinum catalyst synthesized in the preparation example and 10 mL of isopropyl alcohol were placed in a container and completely dispersed using an ultrasonic disperser for 10 minutes. 3.0 mmol of oleylamine (OAm) was added to the solution, placed on a stirrer, and stirred at 500 rpm at room temperature for 12 hours. Afterward, the supernatant was removed using a centrifuge, and the solid was completely dried under vacuum at room temperature. After grinding the solid into a fine powder, 0.5 g portions were transferred to a high-temperature synthesis container, and the OAm-Pt-30 catalyst was prepared through a heat treatment process at 350 °C for 1 hour. At this time, the platinum content contained in the OAm-Pt-30 catalyst was 2.6 wt%.
[0159] A platinum catalyst was prepared in the same manner as in Example 1-1 above, except that the amount of oleylamine added during the manufacturing process was 3.0 mmol.
[0160] Examples 1-4: OAm-Pt-50 catalyst, oleylamine 5.0 mmol
[0161] 1 g of the platinum catalyst synthesized in the preparation example and 10 mL of isopropyl alcohol were placed in a container and completely dispersed using an ultrasonic disperser for 10 minutes. 5.0 mmol of oleylamine (OAm) was added to the solution, placed on a stirrer, and stirred at 500 rpm at room temperature for 12 hours. Afterward, the supernatant was removed using a centrifuge, and the solid was completely dried under vacuum at room temperature. After grinding the solid into a fine powder, 0.5 g portions were transferred to a high-temperature synthesis container, and the OAm-Pt-50 catalyst was prepared through a heat treatment process at 350 °C for 1 hour. At this time, the platinum content contained in the OAm-Pt-50 catalyst was 2.6 wt%.
[0162] A platinum catalyst was prepared in the same manner as in Example 1-1 above, except that the amount of oleylamine added during the manufacturing process was 5.0 mmol.
[0163] Example 2: Surface-amine treated heterogeneous composite catalyst (change in amine type)
[0164] Example 2-1: EDAm-Pt-50 catalyst, Ethylenediamine 5.0 mmol
[0165] A platinum catalyst was prepared in the same manner as in Examples 1-4 above, except that ethylenediamine was used instead of oleylamine added during the manufacturing process.
[0166] Example 2-2: BAm-Pt-50 catalyst, Benzylamine 5.0 mmol
[0167] A platinum catalyst was prepared in the same manner as in Examples 1-4 above, except that Benzylamine was used instead of oleylamine added during the manufacturing process.
[0168] Examples 2-3: t-BAm-Pt-50 catalyst, Tert-butylamine 5.0 mmol
[0169] A platinum catalyst was prepared in the same manner as in Examples 1-4 above, except that Tert-butylamine was used instead of oleylamine added during the manufacturing process.
[0170] Examples 2-4: CHAm-Pt-50 catalyst, Cyclohexylamine 5.0 mmol
[0171] A platinum catalyst was prepared in the same manner as in Examples 1-4 above, except that Cyclohexylamine was used instead of oleylamine added during the manufacturing process.
[0172] Comparative Example 1: OAm-Pt-0 catalyst, oleylamine 0 mmol (no surface amine treatment)
[0173] 1 g of the platinum catalyst synthesized in the preparation example and 10 mL of isopropyl alcohol were placed in a container and completely dispersed using an ultrasonic disperser for 10 minutes. Afterward, the mixture was placed on a stirrer and stirred at 500 rpm at room temperature for 12 hours. Subsequently, the supernatant was removed using a centrifuge, and the solid was completely dried under vacuum at room temperature. After grinding the solid into a fine powder, 0.5 g portions were transferred to a high-temperature synthesis container, and the control catalyst OAm-Pt-0 was prepared through a heat treatment process at 350 ℃ for 1 hour. At this time, the platinum content contained in the OAm-Pt-0 catalyst was 3.0 wt%.
[0174] Comparative Example 2: OcAc-Pt-50 catalyst, 5.0 mmol oleic acid (surface oleic acid treated)
[0175] A platinum catalyst was prepared in the same manner as in Examples 1-4 above, except that oleic acid was used instead of oleylamine added during the manufacturing process.
[0176] [Test Example]
[0177] Test Example 1: Size analysis of platinum nanoparticles in supported catalyst
[0178] Figure 2 shows the STEM images and platinum nanoparticle size distributions of the OAm-Pt-0 catalyst of Comparative Example 1 of the present invention and the OAm-Pt-a (a = 05, 10, 30, 50) catalysts of Examples 1-1 to 1-4. Scanning transmission electron microscopy (STEM) analysis was performed to analyze the size of platinum nanoparticles within the heterogeneous platinum complex catalyst, and the results are shown in Figure 2.
[0179] Referring to FIG. 2, it was confirmed that for all platinum-supported catalysts synthesized in Comparative Example 1 (OAm-Pt-0), Example 1-1 (OAm-Pt-05), Example 1-2 (OAm-Pt-10), Example 1-3 (OAm-Pt-30), and Example 1-4 (OAm-Pt-50), uniform platinum nanoparticles with an average size of approximately 1.7–1.9 nm were evenly dispersed on the surface of the alumina support. There was almost no difference in platinum nanoparticle size between samples.
[0180] Test Example 2: Analysis of the amount of active sites exposed on the surface of platinum nanoparticles
[0181] To quantitatively analyze the amount of active sites exposed on the surface of platinum nanoparticles, the analysis was performed using the carbon monoxide (CO) chemisorption method utilizing the BELCAT-II instrument from MicrotracBEL. This analytical method is based on the principle that CO gas is not adsorbed onto the Al2O3 support but is adsorbed only to platinum atoms exposed on the surface of the supported catalyst at a 1:1 ratio. Specifically, the control catalyst synthesized in Comparative Example 1 or the surface amine-treated catalysts synthesized in Examples 1-1 to 1-4 were placed in the instrument with approximately 50 mg of platinum catalyst and reduced with hydrogen gas at 200°C for 2 hours. Subsequently, the temperature was lowered to 50°C, and CO gas was injected in a pulsed manner to calculate the amount of CO gas chemisorbed by the sample. Table 1 lists the CO adsorption amount for each catalyst, the platinum dispersion calculated based on this, and the ratio of platinum sites obscured by amine.
[0182] catalyst CO adsorption capacity [cm² 3 g cat -1 ] Platinum dispersion [%] Percentage of platinum sites masked by amines [%] Comparative Example 1 OAm-Pt-0 2.40 68.6 0 Example 1-1 OAm-Pt-05 2.35 67.2 2.0 Examples 1-2 OAm-Pt-10 2.19 66.5 3.1 Examples 1-3 OAm-Pt-30 1.89 62.8 8.5 Examples 1-4 OAm-Pt-50 1.75 57.9 15.6
[0183] Referring to Table 1 above, the surface amine-treated catalysts corresponding to Examples 1-1 to 1-4 exhibited lower CO adsorption and platinum dispersion compared to the catalyst in Comparative Example 1, which was not surface amine-treated. Furthermore, it can be observed that even within the surface amine-treated samples, the CO adsorption and platinum dispersion gradually decrease as the amount of added oleylamine increases. As confirmed in Figure 2 above, since the average size of platinum nanoparticles is similar for all catalysts, the decrease in platinum dispersion due to surface amine treatment is because the amine residue covers some active sites on the platinum surface, thereby reducing the number of exposed platinum atoms.
[0184] Through this, when calculating the ratio of surface platinum atoms covered by amine, it can be confirmed that as the amount of amine added during the surface amine treatment process gradually increases, the number of covered platinum sites also gradually increases.
[0185] Test Example 3: Analysis of Types of Active Sites Exposed to the Surface of Platinum Nanoparticles
[0186] Active sites exposed on the surface of platinum nanoparticles can be broadly classified into well-coordinated sites (WC) and under-coordinated sites (UC), and the two types of active sites can be distinguished by the characteristic that peaks appear at different wavenumbers when CO gas adsorbed on the platinum surface is observed using infrared spectroscopy.
[0187] FIG. 3a is the CO adsorption infrared spectroscopic spectrum of the OAm-Pt-0 catalyst of Comparative Example 1 of the present invention and the OAm-Pt-a (a = 05, 10, 30, 50) catalyst of Examples 1-1 to 1-4.
[0188] Referring to FIG. 3a, the analysis method involves placing approximately 25 mg of the surface amine-treated platinum catalyst synthesized in Comparative Example 1 or Examples 1-1 to 1-4 into a sample cell in the high-temperature chamber of an iS-50 infrared spectrometer and reducing it with 5% hydrogen gas at 200 °C for 2 hours. Subsequently, the temperature is lowered to 50 °C, and the pre-adsorption peak is measured under argon gas. After flowing 5% CO gas for 5 minutes and then argon gas for 5 minutes to remove all unadsorbed CO gas, the peak is analyzed to obtain only the peak for CO gas chemisorbed on the catalyst. The infrared spectroscopic peak of CO adsorbed on the platinum surface is in the high wavenumber range (2084–2097 cm⁻¹). -1 CO peak adsorbed at high coordination sites appearing in ) and low wavenumber range (2033-2071 cm⁻¹) -1 It can be separated by the CO peak adsorbed at the low coordination number site appearing in ). The results of the infrared spectroscopic analysis of CO adsorption for each catalyst are shown in Figure 3a and Table 2.
[0189] catalyst Surface exposure active point ratio WC / UC ratio WC [%] UC [%] Comparative Example 1 OAm-Pt-0 20 80 0.25 Example 1-1 OAm-Pt-05 23 77 0.30 Examples 1-2 OAm-Pt-10 24 76 0.32 Examples 1-3 OAm-Pt-30 27 73 0.37 Examples 1-4 OAm-Pt-50 29 71 0.40
[0190] Referring to Fig. 3a, it can be observed that in the spectrum of the catalyst of Comparative Example 1, peaks corresponding to high-coordinate sites at high wavenumbers and peaks corresponding to low-coordinate sites at low wavenumbers are distinguished. When looking at the CO adsorption spectrum after surface amine treatment, it was observed that the relative proportion of peaks corresponding to high-coordinate sites gradually increased as the amount of oleylamine added during surface amine treatment increased. To quantitatively analyze these observations more precisely, an analysis of the ratio of surface active sites was conducted through CO adsorption peak separation as shown in Table 2. As a result, a gradual increase in the ratio of high-coordinate sites and a decrease in the ratio of low-coordinate sites were confirmed depending on the amount of oleylamine added during surface amine treatment.
[0191] Through this, it was confirmed that surface amine treatment selectively adsorbs to low-coordinated sites among the surface active sites of platinum nanoparticles, particularly increasing the proportion of platinum active sites at relatively exposed high-coordinated sites on the surface.
[0192] Test Example 4: Analysis of Amine Residue on Supported Catalyst Surface
[0193] Figure 4 is the transmitted infrared spectroscopic spectrum of the OAm-Pt-0 catalyst of Comparative Example 1 of the present invention and the OAm-Pt-a (a = 05, 10, 30, 50) catalyst of Examples 1-1 to 1-4.
[0194] Referring to FIG. 4, amine functional groups were analyzed using transmission infrared spectroscopy to analyze amine residues present on the surface of the supported catalyst after amine treatment. 0.5 mg of the surface amine-treated catalyst synthesized in Comparative Example 1 or Examples 1-1 to 1-4 and 3.5 mg of KBr were mixed while being finely ground into a powder, then formed into a thin pellet, and transmission spectra were obtained using an infrared spectrometer. The transmission spectra for all catalysts are shown in FIG. 4.
[0195] As a result, as the amount of oleylamine added during the surface amine treatment process increased, peaks corresponding to the functional groups of oleylamine were observed gradually more clearly, which confirmed that amine residues remained on the surface of the supported catalyst.
[0196] Test Example 5: Additional Analysis of Amine Residue on Supported Catalyst Surface
[0197] Figure 5 is an elemental mapping image based on energy-dispersive spectroscopy of the OAm-Pt-50 catalyst of Examples 1-4 of the present invention.
[0198] Referring to Fig. 5, elemental mapping of Al, Pt, and N on the surface of the catalyst synthesized in Examples 1-4 was used to further analyze the amine residue present on the surface of the supported catalyst after amine treatment.
[0199] As a result, it was confirmed that N element-based materials corresponding to oleyl amine residues were evenly dispersed on the surface of the supported catalyst, and through this, it was confirmed that amine residues were present on the surface of the supported catalyst after surface amine treatment.
[0200] Test Example 6: Production of Chiral Compounds via Enantiomer-Selective Heterogeneous Complex Catalytic Reaction
[0201] FIG. 8a shows the catalytic reaction after enantiomer-selective hydrogenation of the OAm-Pt-0 catalyst of Comparative Example 1 of the present invention and the OAm-Pt-a (a = 05, 10, 30, 50) catalysts of Examples 1-1 to 1-4. ee FIG. 8b is a graph showing [the process], FIG. 8b is a diagram showing the production of a chiral compound through the enantiomer-selective heterogeneous complex catalytic reaction of the present invention, and FIG. 9 is a diagram showing the result after the catalytic reaction following the enantiomer-selective hydrogenation reaction of the catalyst according to Examples 1-4, Examples 2-1 to 2-4, Comparative Example 1, and Comparative Example 2 of the present invention. ee This is a graph showing .
[0202] Referring to Figures 8a and 8b, the amine-treated catalysts prepared in Examples 1-1 to 1-4 or the control catalyst prepared in Comparative Example 1 were placed in a tube furnace and reduced with 5% hydrogen gas at 200 °C for 2 hours. 30 mg of the reduced platinum-supported catalyst and 8 mL of an acetic acid solution containing 4 mg of the chiral modifier cinchonidine were placed in a three-necked flask. The chiral catalyst was prepared by stirring at 150 rpm while flowing hydrogen gas through the solution for 10 minutes. Subsequently, 2 mL of an acetic acid solution containing 0.03 mL of the reactant methyl pyruvate was injected, the stopcock was closed, and the mixture was stirred at 500 rpm to predominantly obtain the chiral compound (R)-methyl lactate. The above process was performed at room temperature under a hydrogen pressure of 1 bar. The catalytic reaction results were analyzed using gas chromatography equipped with a Chirasil-Dex CB capillary column (CP7502, 25 m x 0.25 mm x 0.25 μm, Agilent), and the enantiomeric excess, an indicator of enantiomer selectivity, ( ee In the case of ), it was measured after reaching a conversion rate of 100%. ee was calculated by the following Equation 1, and each catalyst ee It is shown in Table 3.
[0203] [Equation 1]
[0204] ee (%) =
[0205] In the above equation, [R] and [S] represent the production amounts of the mirror-image optical isomer products, R-methyl lactate and S-methyl lactate, respectively.
[0206] catalyst Conversion Rate [%] ee [%] WC / UC ratio Comparative Example 1 OAm-Pt-0 100 77 0.25 Example 1-1 OAm-Pt-05 100 84 0.30 Examples 1-2 OAm-Pt-10 100 86 0.32 Examples 1-3 OAm-Pt-30 100 89 0.37 Examples 1-4 OAm-Pt-50 100 90 0.40 Example 2-1 EDAm-Pt-50 100 90 0.38 Example 2-2 BAm-Pt-50 100 90 0.39 Examples 2-3 t-BAm-Pt-50 100 92 0.85 Examples 2-4 CHAm-Pt-50 100 92 0.62
[0207] In Table 3, Comparative Example 1 (OAm-Pt-0) is a control catalyst without surface amine treatment, and when performing an enantiomer-selective catalytic reaction, approximately 77% of ee ...was shown. For the surface amine-treated catalyst samples corresponding to Examples 1-1 to 1-4 and Examples 2-1 to 2-4, 84-90%, which is at least 7% higher than Comparative Example 1 ee It showed, and as the amount of oleylamine added during the amine treatment process increased, gradually higher ee It shows, but when a larger amount of amine than the amount added in Examples 1-3 is added, it becomes nearly saturated ee It represented.
[0208] Through this, it is confirmed that the catalytic surface amine treatment method has a positive effect on improving enantiomer selectivity, which is attributed to the increase in the ratio of high-coordination sites exposed on the surface of platinum nanoparticles through surface amine treatment, as confirmed in Figure 3a and Table 2 above.
[0209] Referring to Figure 9, the linear positive correlation between enantiomer selectivity and the exposed WC / UC ratio indicates that the promoting effect of OAm treatment was preferentially deposited at the UC sites on the catalyst surface. In addition, as a result of verifying the amine treatment effect using various amine compounds, it was confirmed that catalytic performance was enhanced in all types of amines, and it was confirmed that this catalyst can be utilized by extending to enantiomer-selective catalytic reactions.
[0210] Table 4 shows the chiral selectivity according to the type of chiral modifier ( ee It represents ).
[0211] chiral modifiers Main product Chiral selectivity ( ee [%]) OAm-Pt-0 OAm-Pt-50 Cinchonidine (R)-methyl lactate 77 90 Cinchonine (S)-methyl lactate 51 72 Quinine (R)-methyl lactate 80 95 Quinidine (S)-methyl lactate 57 83
[0212] Referring to Table 4 above, one of the key factors determining enantiomer selectivity is the adsorption of the chiral modifier cinchonidin onto the platinum surface. As previously mentioned, cinchonidin, cinchonine, quinine, and quinidine were confirmed to exhibit significantly higher catalytic performance compared to the comparative example without amine treatment. Therefore, this catalyst can be utilized by extending enantiomer-selective catalytic reactions using various chiral modifiers.
[0213] This is because, since it is adsorbed onto the platinum surface through the quinoline ring portion with a large volume within the molecule, high-coordination active sites rather than low-coordination active sites act as sites where the quinoline ring is adsorbed flatly and stably.
[0214] Through this, it was confirmed that the surface amine treatment method of the present invention induces stable adsorption of chiral modifiers such as cinconidine, cinconin, quinine, and quinidine due to an increase in the ratio of high-coordination number active sites on the catalyst surface, thereby improving enantiomer selectivity compared to the catalyst before amine treatment.
[0215] Test Example 7: Catalyst Reuse Experiment
[0216] Figure 6 shows the conversion rate according to the reusable catalytic reaction of the OAm-Pt-50 catalyst of Examples 1-4 of the present invention and ee This is a graph summarizing [it].
[0217] Referring to Fig. 6, the amine-treated catalyst (OAm-Pt-50) prepared in Examples 1-4 was placed in a tube furnace and reduced with 5% hydrogen gas at 200 °C for 2 hours. 100 mg of the reduced catalyst and 8 mL of an acetic acid solution containing 4 mg of cinchonidine, a chiral modifier, were placed in a three-necked flask. The chiral catalyst was prepared by stirring at 150 rpm while flowing hydrogen gas through the solution for 10 minutes. Subsequently, 2 mL of an acetic acid solution containing 0.03 mL of the reactant methyl pyruvate was injected, the stopcock was closed, and the mixture was stirred at 500 rpm for 10 minutes to predominantly obtain the chiral compound (R)-methyl lactate. The above process was performed at room temperature under a hydrogen pressure of 1 bar. For the catalyst reuse experiment, the catalyst in the reaction-completed solution was separated using a centrifuge, washed with 10 mL of acetic acid, and mixed. Subsequently, the supernatant was removed using a centrifuge once more, transferred back to a three-necked flask, and 8 mL of acetic acid solution containing 4 mg of cinchonidine was added. A chiral catalyst was prepared by stirring at 150 rpm while flowing hydrogen gas through the solution for 10 minutes, and a second catalyst reuse experiment was performed by injecting 2 mL of acetic acid solution containing 0.03 mL of the reactant, methyl pyruvate. The above process of catalyst separation and subsequent reuse reaction experiments was repeated 10 times for a total of 10 catalyst reuse tests, and the results of the catalytic reaction are shown in Figure 6. Although a negligible decrease in conversion rate of less than 5% was observed starting from approximately the 8th catalyst reuse experiment, a high rate of nearly 90% was maintained. ee It was confirmed that it remained intact even during a total of 10 reusable catalyst reactions.
[0218] Through this, it was confirmed that the positive effects of surface amine treatment are well maintained even when the surface amine-treated heterogeneous composite catalyst is reused multiple times.
[0219] Test Example 8: Test for maintaining catalyticity under catalytic reaction conditions (high hydrogen pressure)
[0220] FIG. 7a shows the catalytic reaction according to hydrogen pressure conditions using the OAm-Pt-0 catalyst of Comparative Example 1 of the present invention and the OAm-Pt-50 catalyst of Examples 1-4. ee This is a graph showing, and FIG. 7b is a graph showing the conversion rate (won) in the enantiomer-selective hydrogenation of methyl pyruvate with respect to the OAm-Pt-50 catalyst using the OAm-Pt-50 catalyst of Examples 1-4 of the present invention and ee This is a graph showing the time dependence of (rectangle).
[0221] Referring to Fig. 7a, for the OAm-Pt-50 catalyst prepared in Examples 1-4 to the OAm-Pt-0 catalyst prepared in Comparative Example 1, 30 mg of the sample and 5 mL of an acetic acid solution containing 4 mg of cinchonidine, a chiral modifier, were placed in a high-pressure vessel. The chiral catalyst was prepared by stirring at 150 rpm while flowing hydrogen gas through the solution for 10 minutes. Subsequently, the hydrogen pressure was raised to 3 to 10 bar, and 5 mL of an acetic acid solution containing 0.03 mL of the reactant methyl pyruvate was injected and stirred at 500 rpm to predominantly obtain the chiral compound (R)-methyl lactate. The enantiomer selectivity according to hydrogen pressure is shown in Fig. 7a. The above process was performed at room temperature.
[0222] As a result, the surface amine-treated catalyst prepared in Examples 1-4 was about 12% higher than the catalyst prepared in Comparative Example 1 over a wide hydrogen pressure range of 1-10 bar. ee It was confirmed that the surface amine treatment effect is well maintained even under high hydrogen pressure conditions.
[0223] Referring to Fig. 7b, from the beginning of the reaction until the end, high eeIt was confirmed that the amine modification effect was maintained during the catalytic reaction.
[0224] The scope of the present invention is defined by the claims set forth below rather than by the detailed description above, and all modifications or variations derived from the meaning and scope of the claims and equivalent concepts thereof should be interpreted as being included within the scope of the present invention.
Claims
Claim 1 (a) a step of preparing a first mixture by mixing and stirring a metal precursor, a metal oxide, and a first solvent; (b) a step of preparing a first powder by removing the first solvent from the first mixture and grinding it; (c) a step of preparing a metal oxide supported with metal nanoparticles by heat-treating the first powder under an inert gas; (d) a step of preparing a second mixture by mixing the metal oxide supported with metal nanoparticles, an amine compound, and a second solvent; (e) a step of preparing a second powder by removing the second solvent from the second mixture and grinding it; (f) a step of preparing a first heterogeneous composite catalyst by heat-treating the second powder; (g) a step of reducing the first heterogeneous composite catalyst in the presence of hydrogen; and (h) a step of preparing a second heterogeneous composite catalyst by mixing the reduced first heterogeneous composite catalyst with a chiral modifier and stirring it in the presence of hydrogen; wherein the first heterogeneous composite catalyst comprises a metal oxide; A method for preparing a heterogeneous composite catalyst comprising: metal nanoparticles supported on the metal oxide; and a nitrogen-containing hydrocarbon compound formed on a portion of the surface of the metal nanoparticles. Claim 2 A method for manufacturing a heterogeneous composite catalyst according to claim 1, characterized in that the nitrogen-containing hydrocarbon compound covers a portion of the active sites exposed on the surface of the metal nanoparticles. Claim 3 A method for manufacturing a heterogeneous composite catalyst according to claim 2, characterized in that the active site comprises a well-coordinated site (WC) and an under-coordinated site (UC). Claim 4 A method for manufacturing a heterogeneous composite catalyst according to claim 3, characterized in that the nitrogen-containing hydrocarbon compound is located at the low coordination number site active site and covers the low coordination number site active site. Claim 5 A method for manufacturing a heterogeneous composite catalyst according to claim 4, characterized in that the ratio of high-coordinated number sites to low-coordinated number sites (WC / UC) increases as the nitrogen-containing hydrocarbon compound increases. Claim 6 A method for manufacturing a heterogeneous composite catalyst according to claim 5, characterized in that the heterogeneous composite catalyst is used to selectively produce one of the enantiomers. Claim 7 A method for preparing a heterogeneous composite catalyst according to claim 6, characterized in that the selectivity of enantiomers changes according to the ratio (WC / UC) of the high-coordination number active site to the low-coordination number active site. Claim 8 A method for producing a heterogeneous composite catalyst according to claim 1, characterized in that the nitrogen-containing hydrocarbon compound comprises -NH, -CH2 and -CH3 groups. Claim 9 A method for manufacturing a heterogeneous composite catalyst according to claim 1, characterized in that the nitrogen-containing hydrocarbon compound is produced by heat-treating an amine compound formed on a portion of the surface of the metal nanoparticle. Claim 10 A method for manufacturing a heterogeneous composite catalyst according to claim 9, characterized in that the amine compound comprises one or more selected from aliphatic amine compounds and aromatic amine compounds. Claim 11 A method for manufacturing a heterogeneous composite catalyst according to claim 10, characterized in that the aliphatic amine compound is a compound represented by the following structural formula 1: [Structural Formula 1] In the above structural formula 1, R 1 is a linear or branched C1 to C15 alkylene group, and R 2 is an atom bond, or and, R 3 The valence is a linear or branched C1 to C15 alkylene group, and X is a hydrogen atom or -NH2. Claim 12 A method for manufacturing a heterogeneous composite catalyst according to claim 10, characterized in that the aromatic amine compound is a compound represented by the following structural formula 2: [Structural Formula 2] In the above structural formula 2, R 4 The valence bond is a linear or branched C1 to C5 alkylene group or a C6 to C20 arylene group, and R 5 is an atom bond, or and, R 6 is a C6 to C20 arylene group, and R 7 The valence is a linear or branched C1 to C5 alkylene group or a C6 to C20 arylene group, and Y is a hydrogen atom or -NH2. Claim 13 A method for manufacturing a heterogeneous composite catalyst according to claim 1, characterized in that the metal oxide comprises one or more selected from the group consisting of silica (SiO2), alumina (Al2O3), silica-alumina (SiO-2-Al2O3), titanium oxide (TiO2), zirconium oxide (ZrO2), cerium oxide (CeO2), and magnesium oxide (MgO). Claim 14 A method for manufacturing a heterogeneous composite catalyst according to claim 1, characterized in that the metal nanoparticles comprise one or more selected from the group consisting of platinum (Pt), palladium (Pd), ruthenium (Ru), rhodium (Rh), iridium (Ir), rhenium (Re), cobalt (Co), tungsten (W), vanadium (V), nickel (Ni), gold (Au), silver (Ag), and copper (Cu). Claim 15 A method for manufacturing a heterogeneous composite catalyst according to claim 1, characterized in that the heterogeneous composite catalyst further comprises a chiral modifier formed on another portion of the surface of the metal nanoparticle. Claim 16 A method for producing a heterogeneous composite catalyst according to claim 15, characterized in that the chiral modifier comprises one or more selected from the group consisting of quinoline-based optical isomers, indole-based optical isomers, naphthylene-based optical isomers, indole-based optical isomers, and pyrrolidine-based optical isomers. Claim 17 A method for manufacturing a heterogeneous composite catalyst according to claim 15, characterized in that the chiral modifier comprises one or more selected from the group consisting of compounds represented by the following chemical formulas 1 to 22. Claim 18 delete Claim 19 delete Claim 20 A method for synthesizing a chiral compound comprising: a step of preparing a heterogeneous composite catalyst according to the method for preparing a heterogeneous composite catalyst of claim 1; and a step of selectively preparing a chiral compound among enantiomers by contacting a compound represented by the structural formula 3 below with said heterogeneous composite catalyst; [Structural Formula 3] In the above structural formula 3, R 8 and R 9 Each is independently a halogen atom, a substituted or unsubstituted C1 to C5 alkyl group, or a substituted or unsubstituted C6 to C30 aryl group, or forms a ring with an adjacent group, and A is -(C=O)-, -CR 10 R 11 -, -NR 12 - or -O- and, where, R 10 and R 11 Each is independently a hydrogen atom, a halogen atom, or a substituted or unsubstituted alkoxy group, and R 12 is a hydrogen atom, or a substituted or unsubstituted alkyl group, and the group corresponding to the substitution is a C1 to C5 alkyl group or a C6 to C14 aryl group, n is an integer from 1 to 3, and if n is 2 or more, the 2 or more A are the same or different from each other.
